Identity and Upbringing in South Asian Muslim Families Insights from Young People and their Parents in Britain - Franceschelli, Michela; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
What is it like to grow up as a South Asian British Muslim today? What are the experiences of South Asian Muslim parents bringing up their children in contemporary Britain? Identity and Upbringing in South Asian Muslim Families explores these questions within the context of the series of events which, from 9/11 to the recent upsurge of the Islamic State, have affected the perceptions and the identity of Muslims around the world. Franceschelli reveals the complex range of negotiations behind the coming of age of South Asian Muslim teenagers and reflects on the changes and continuities between their life experiences, priorities and aspirations compared to their parents' generation. Based on primary research with South Asian Muslim young people and parents, this book highlights the importance of Islam to upbringing; the shifting value of South Asian cultural norms in Britain; and the persistent influence of class in shaping inequalities amongst families and on young people's experiences of growing up.
1. Introduction -- 2. Constructing a British Muslim identity -- 3. 'Being Modern and Modest': Identity and Negotiations -- 4. Love Relationships and Marriage: The role of agency, Islam and culture in the selection of a suitable partner -- 5. Islamic Capital: The role of Islam and social class in Upbringing -- 6. 'Because Education is Everything': capacity to aspire and inequality -- 7. Conclusion: Questions of identity and upbringing .
Keywords: Ethnicity